PENGUATAN AKUNTABILITAS WAKAF (ILUSTRASI PADA KASUS WAKAF UANG DAN WAKAF SAHAM) - Baihaqi, Jadzil; Islamiah, Makrufah Hidayah; Munandar, Muhammad Aris (Department of Accounting, Faculty of Economics and Business, Universitas Tadulako, 2021)
Accountability is still a weakness in waqf management. Not all nazirs can apply the Statement of Financial Accounting Standards (PSAK) No. 112 concerning Waqf Accounting as a standard in preparing financial statements for waqf management. Therefore, educational efforts and technical guidance are needed for the Nazirites, especially the money waqf nazirs (including stock waqf), whose potential is currently very large. This research is expected to provide experience in implementing PSAK No. 112 on waqf transactions. After Nazir can make correct waqf financial statements, it is hoped that people will be more interested in waqf money because waqf is managed in an accountable and transparent manner. The purpose of this study is to illustrate the application of PSAK No. 112 concerning Waqf Accounting on cash waqf transactions and stock waqf. This research uses a literature study approach. The results of this study are illustrations of journals and financial reports for cash waqf transactions and share waqf following the criteria for recognition, measurement, valuation, and presentation in financial statements based on PSAK No. 112 concerning Waqf Accounting.